The relationship between students' part-time work experiences and their graduate attributes - Gross, Victoria Louise (Organisational Psychology, 2014)
This study examined the relationship between work experience and the development of eight graduate attributes among postgraduate students in the faculties of Humanities and Commerce at the University of Cape Town (N = 167). A quantitative research approach was used and data gathered through a questionnaire using a 6-point Likert scale and a work experience grid that was developed by the researcher for the purposes of this study. In order to measure the data, a series of analyses were conducted. Results revealed non-significant relationships between the length and nature of work experience and the development of the perceived level of the eight graduate attributes. Findings furthermore indicated that although graduates were still developing these attributes, it was not as a result of work experience. This study highlights the complexity and many nuances surrounding the development of graduate attributes within higher education. The findings also provide a basis for future research into work experience as an antecedent of attribute development.